2021
DOI: 10.1111/dom.14321
|View full text |Cite|
|
Sign up to set email alerts
|

HbA1c and brain health across the entire glycaemic spectrum

Abstract: Aim: To understand the relationship between HbA1c and brain health across the entire glycaemic spectrum. Materials and Methods:We used data from the UK Biobank cohort consisting of 500,000 individuals aged 40-69 years. HbA1c and diabetes diagnosis were used to define baseline glycaemic categories. Our outcomes included incident all-cause dementia, vascular dementia (VD), Alzheimer's dementia (AD), hippocampal volume (HV), white matter hyperintensity (WMH) volume, cognitive function and decline.The reference gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 36 publications
7
44
1
Order By: Relevance
“…These associations were present in our fully adjusted models for all neuroimaging outcomes, except for gFA (a measure of white matter integrity) and the amygdala (region associated with emotional processing and fear-related memories). These findings largely agree with previous studies of the association between diabetes and neuroimaging outcomes in the UKB [6, 7]. A key difference between our study and that of Cox et al though, is that we observed no relationship between diabetes and gFA, but they did.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These associations were present in our fully adjusted models for all neuroimaging outcomes, except for gFA (a measure of white matter integrity) and the amygdala (region associated with emotional processing and fear-related memories). These findings largely agree with previous studies of the association between diabetes and neuroimaging outcomes in the UKB [6, 7]. A key difference between our study and that of Cox et al though, is that we observed no relationship between diabetes and gFA, but they did.…”
Section: Discussionsupporting
confidence: 92%
“…This discrepancy could be due to differences in modelling approaches (including covariate adjustment), sample size (∼10,000 vs our sample of maximum ∼40,000) and definition of diabetes (self-reported vs use of a validated algorithm plus HbA1c measurements). Our study also investigated a much wider range of neuroimaging parameters compared to at least one of the earlier studies [7], which only included hippocampal and white matter hyperintensity volumes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, mediation effects were observed on glycated hemoglobin A (HbA1c) and glucose, which were biomarkers of diabetes. High HbA1c level (hyperglycaemia) is associated with worse brain health and cognitive functions 52 , such as memory loss, poorer processing speed, attention, concentration, and executive functions 53,54 . As the primary source of energy for the brain, glucose metabolism plays an important role in the physiological and pathological functioning of the brain 55 .…”
Section: Resultsmentioning
confidence: 99%